Inibição de formação de biofilme bacteriano através de lectinas vegetais - Carneiro, Victor Alves (2007)
Natural and complementary medicine, especially phytotherapy, is becoming more and more useful to fulfill the needs of great part of the population when it comes to oral health, particularly in the developing countries. Among the phytotherapics, lectins may be valuable as anti-plaque and antimicrobial agents, since they can be intimately related with inference in biofilm formation, given that these proteins recognize carbohydrates in a specific and reversible way. Within that context, this study aimed to test the ability of five lectins (extracted from Canavalia ensiformis, Canavalia maritima, Cymbosema roseum, Acacia farnesiana and Hypnea cervicornis) in inhibiting the formation of biofilm and killing oral microorganisms(Streptococcus sanguis ATCC10556 e S. mutans UA159). The antimicrobial activity of the five lectins tested was determined by the convetional test of microdilution in polystyrene plaques. The lectin concentrations assayed against the microorganisms varied from 2mg/mL to 31. 5μ g/mL. To evaluate the adherence, a semi -quantitative assay was perfomed within microtitulation plaques (96 wells), to where were added 100μL of each lectin, and then 100μL of bacterial suspension (108 CFU/mL). This material was incubated in 10% CO 2 atmosphere at 37ºC. Adherence was revealed and quantified by violet crystal staining. Absorption of violet crystal was determined by spectophotometry (595nm). Only ConA presented bactericide or bacteriostatic activity against the strains tested. The assay of inhibition of biofilm formation revealed that almost all lectins had this kind of activity, reducing the adherence in a significant way (p<0.05). ConA had no effect on the formation of biofilm for any bacteria tested.